2011
DOI: 10.1002/jsfa.4342
|View full text |Cite
|
Sign up to set email alerts
|

Ripening-associated changes in the amounts of starch and non-starch polysaccharides and their contributions to fruit softening in three banana cultivars

Abstract: Banana softening is a consequence of starch degradation and the accumulation of soluble sugars in a cultivar-dependent manner. However, contributions from cell wall-related changes cannot be disregarded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 24 publications
6
43
0
11
Order By: Relevance
“…However, once initiated its hydrolysis is relatively independent of ethylene concentrations within the fruit tissue. Also, relationships between ethylene and starch metabolism are not straightforward, as starch degradation in bananas, for example, is coordinated with that of cell wall softening (Shiga et al, 2011).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…However, once initiated its hydrolysis is relatively independent of ethylene concentrations within the fruit tissue. Also, relationships between ethylene and starch metabolism are not straightforward, as starch degradation in bananas, for example, is coordinated with that of cell wall softening (Shiga et al, 2011).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…Fruit firmness is an important criterion for determining the edible quality and ripeness of bananas. It has been reported that coordinated degradation of pectic, hemicellulosic polysaccharides in the cell wall and starch is the main cause of banana fruit softening (Mbeguie‐A‐Mbeguie et al ., ; Shiga et al ., ). Starch degradation during the postharvest ripening provides carbon for the production of sucrose and flavour‐producing volatile compounds (Saraiva et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…From harvest to market, losses can reach up to 50% of the total volume produced (SEBRAE 2008). In unripe bananas, starch is the main component (around 220 mg per gram of fruit; Shiga and others 2011). During ripening, the starch is converted into soluble sugars contributing to pulp softening.…”
Section: Introductionmentioning
confidence: 99%